Quantification of the impact of port activities on PM10 levels at the port-city boundary of a mediterranean city. (1st March 2021) - Clemente, Á.; Yubero, E.; Galindo, N.; Crespo, J.; Nicolás, J.F.; Santacatalina, M.; Carratala, A.
Abstract: The main objective of this work was to quantify the impact of handling of bulk materials on PM10 levels measured at the port-city border of Alicante (Spain), located on the western Mediterranean coast. To achieve that goal, 355 PM10 samples were collected at the perimeter of the harbor of Alicante from March 2017 to February 2018. A 181 sample subgroup was chemically characterized in order to perform a source apportionment study with the EPA PMF 5.0 model. Eight factors were identified, two of them directly related to the handling of bulk materials ( Limestone + gypsum and Clinker ), accounting jointly for 35% of the average PM10 concentration. A Road traffic factor was the second highest contributor to PM10 levels (17%) while the Shipping emissions factor accounted for only 6% of the average PM10 mass. Other factors such as Biomass burning+ secondary nitrate and Aged sea salt represented a joint contribution of 25% of the PM10 mass. Results indicate that emission abatement strategies should primarily focus on the reduction of fugitive emissions caused by the handling of bulk materials at the docks. Moreover, scenarios including reductions of more than 50% in bulk handling sources and 10% in other anthropogenic sources would help to reduce anthropogenic exceedances of the daily PM10 limit (50 μg·m −3 ) and to approach to WHO daily PM10 standard (20 μg m −3 ). Highlights: We conducted a PMF source apportionment in the perimeter of a medium sized port. The biggest dock is less than 600 m from the closest neighborhood. Handling of bulk materials was the main anthropogenic PM10 source in the area. Port activities were the main anthropogenic cause of the daily PM10 limit exceedances.